Synergizing the multiple plasmon resonance coupling and quantum effects to obtain enhanced SERS and PEC performance simultaneously on a noble metal–semiconductor substrate. Issue 6 (1st February 2017) - Yang, Tao; Liu, Wenna; Li, Lidong; Chen, Junhong; Hou, Xinmei; Chou, Kuo-Chih
Abstract : TiO2 NTAs@hybrid Au NPs with the synergistic enhancement of the SERS and PEC performance was assembled. This substrate overcame the contradiction effect of the Au NP size on the SERS and PC/PEC performance. Abstract : Aiming to achieve the synergistic enhancement of the surface-enhanced Raman scattering (SERS) and photoelectrocatalytic (PEC) performance on a noble metal–semiconductor, such as Au nanoparticles (NPs)–TiO2 nanotube arrays (TiO2 NTAs@hybrid Au NPs), theoretical calculation and experiments are performed. Theoretical calculation indicates that both the SERS and PEC performance can be enhanced by coupling different sized Au NPs on TiO2 NTAs based on synergizing the multiple plasmon resonance coupling and quantum effects. To further verify this mechanism, TiO2 NTAs@hybrid Au NPs are assembled via synthesis of TiO2 NTAs through the anodic oxidation process, followed by the deposition of different sized Au NPs onto the TiO2 surface simultaneously using physical vapor deposition (PVD) in this work. Such substrates exhibit excellent detection sensitivity towards organic dyes including Rhodamine B (RhB), the organic herbicide dichlorophenoxyacetic acid (2, 4-D) and the organophosphate pesticide methyl-parathion (MP) with high reproducibility, stability and reusability. Meanwhile the PEC performance based on this substrate remains efficient compared with the reported results in the literature. The efficient PEC performance mainly originates from both the quantum effect of Au nanoparticles and the formation of a metal–semiconductor heterojunction. It is proposed that other noble metal–semiconductor complex nanomaterials can also obtain both enhanced SERS and PEC performance based on the above mechanism.